2014
DOI: 10.1124/jpet.114.217281
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Aortic Vasodilation and Sympathetic Prejunctional Facilitation in Epinephrine-Deficient Mice: Selective Impairment of β2-Adrenoceptor Responses

Abstract: It has been suggested that there is a link between epinephrine synthesis and the development of b 2 -adrenoceptor-mediated effects, but it remains to be determined whether this development is triggered by epinephrine. The aim of this study was to characterize b-adrenoceptor-mediated relaxation and facilitation of norepinephrine release in the aorta of phenylethanolamine-Nmethyltransferase-knockout (Pnmt-KO) mice. Catecholamines were quantified by reverse-phase high-performance liquid chromatography-electrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…It might be related to an impaired dobutamine-induced vasodilation through β 2 -adrenergic receptors. This hypothesis is supported by Moreira-Rodrigues et al, who observed that Pnmt-KO mice present a lower β 2 -adrenoceptor protein density in aorta cell membranes than their WT counterparts [8]. Another possibility for the blunted response to dobutamine is a decrease in myocardial contractile reserve.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…It might be related to an impaired dobutamine-induced vasodilation through β 2 -adrenergic receptors. This hypothesis is supported by Moreira-Rodrigues et al, who observed that Pnmt-KO mice present a lower β 2 -adrenoceptor protein density in aorta cell membranes than their WT counterparts [8]. Another possibility for the blunted response to dobutamine is a decrease in myocardial contractile reserve.…”
mentioning
confidence: 80%
“…Only more recently, was an adrenaline-deficient mouse model generated by selectively knocking out the Pnmt gene (Pnmt-KO) [3]. This animal cannot produce adrenaline, but is able to synthesize and maintain normal plasma levels of noradrenaline [5,8]. Studies have shown that Pnmt-KO mice survive to adulthood and breed effectively [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Burns are associated with a high concentration of circulating levels of the catecholamines epinephrine and norepinephrine (27). Epinephrine has been shown to be responsible for β2-adrenoceptor-mediated vasodilation in an animal study (14). Thus, we postulate that propranolol, a non-selective β1-, β 2-adrenoceptor antagonist, is able to inhibit the epinephrine-induced vasodilatation and cause vasoconstriction, resulting in an increased SVRI in pediatric burn patients.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were confirmed in another trial with 11 healthy normotensive male subjects (13). This elevation in SVRI is postulated to be β2-adrenoceptor-mediated (12,14). Hence, propranolol may affect SVRI in severely burned children.…”
Section: Introductionmentioning
confidence: 99%